2014
DOI: 10.1371/journal.pone.0091060
|View full text |Cite
|
Sign up to set email alerts
|

Intentions to Perform Non-Pharmaceutical Protective Behaviors during Influenza Outbreaks in Sweden: A Cross-Sectional Study following a Mass Vaccination Campaign

Abstract: Failure to incorporate the beliefs and attitudes of the public into theoretical models of preparedness has been identified as a weakness in strategies to mitigate infectious disease outbreaks. We administered a cross-sectional telephone survey to a representative sample (n = 443) of the Swedish adult population to examine whether self-reported intentions to improve personal hygiene and increase social distancing during influenza outbreaks could be explained by trust in official information, self-reported healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
36
2
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 36 publications
8
36
2
1
Order By: Relevance
“…Knowledge of protective behaviors against influenza was associated with perceived changes in protective behaviors and an intent to receive an influenza vaccine, which is similar to the study among lay people and nurses [34,35], but inconsistent with previous findings regarding the intent to receive the H1N1 vaccine [4,36]. Although educational level was not associated with perceived changes in protective behaviors, similar to the H1N1 outbreak in Sweden [20], this finding contrasts with those of other studies [32,34,37]. This difference may reflect underlying differences in educational level in the study populations; our study population included more highly educated respondents.…”
Section: Discussioncontrasting
confidence: 93%
See 3 more Smart Citations
“…Knowledge of protective behaviors against influenza was associated with perceived changes in protective behaviors and an intent to receive an influenza vaccine, which is similar to the study among lay people and nurses [34,35], but inconsistent with previous findings regarding the intent to receive the H1N1 vaccine [4,36]. Although educational level was not associated with perceived changes in protective behaviors, similar to the H1N1 outbreak in Sweden [20], this finding contrasts with those of other studies [32,34,37]. This difference may reflect underlying differences in educational level in the study populations; our study population included more highly educated respondents.…”
Section: Discussioncontrasting
confidence: 93%
“…Controlling for demographic variables, perceived fear of H1N1 still existed at the time of the survey and influenced the adoption of washing hands and wearing a face mask in public places against influenza, even though the H1N1 influenza pandemic had declined over one year in a manner similar to previous outbreaks, such as SARS, H5N1 influenza and H1N1 influenza [20,[31][32][33]. Our findings indicated that knowledge was the most common predictor for these four protective behaviors.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…Previous research has also identified the utility of these variables in predicting behavioural responses to respiratory infectious diseases (e.g., Teasdale et al, 2012;Timpka et al, 2014).…”
mentioning
confidence: 99%